Innovative participatory evaluation methodologies to assess and sustain multilevel impacts of two community-based physical activity programs for women in Colombia - María Alejandra Rubio; Paula Guevara-Aladino; Marcela Urbano; Santiago Cabas; Carlos Mejia-Arbelaez; Patricia Rodriguez Espinosa; Lisa G. Rosas; Abby C. King; Scott Chazdon; Olga L. Sarmiento (BMC, 2022)
Abstract Background Community-based physical activity (PA) programs are appealing to women in Latin America and show potential for improving women's health. This study aimed to engage healthy middle-aged women, breast cancer survivors and local stakeholders participating in two publicly funded community-based PA programs in Bogotá, Colombia (Recreovía and My Body) to assess and visually map the perceived barriers, facilitators, and outcomes to promote programs' improvement, scaling and sustainability. Methods We used two participatory action research methods, the 1) Our Voice citizen science method to capture data and drive local change in built and social environmental facilitators and barriers that influence women's engagement in community-based PA; and 2) Ripple Effects Mapping to visually map the intended and unintended outcomes of PA programs. We used thematic analysis to classify the results at the individual, social, and community levels. Results The stakeholders engaged in the participatory evaluation included cross-sector actors from the programs (N = 6) and program users (total N = 34) from the two programs (Recreovía N = 16; My Body N = 18). Program users were women with a mean age of 55.7 years (SD = 8.03), 65% lived in low-income neighborhoods. They identified infrastructure as the main feature affecting PA, having both positive (e.g., appropriate facilities) and negative (e.g., poorly built areas for PA) effects. Regarding program improvements, stakeholders advocated for parks' cleaning, safety, and appropriate use. The most highlighted outcomes were the expansion and strengthening of social bonds and the engagement in collective wellbeing, which leveraged some participants' leadership skills for PA promotion strategies in their community. The facilitated dialogue among program users and stakeholders fostered the sustainability and expansion of the community-based PA programs, even during the COVID-19 pandemic. Conclusions The implementation of both participatory methodologies provided a multidimensional understanding of the programs' impacts and multisectoral dialogues that fostered efforts to sustain the community-based PA programs.